Nutrients, Infectious and Inflammatory Diseases - Helieh S. Oz (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Foodborne disease like salmonellosis and toxoplasmosis are amongst the most significant causes of hospitalization in the U.S. and globally. Gastrointestinal infections alter gut microbiomes and increase permeability to toxins. Various invasions by microbial, fungal, viral and parasitic agents stimulate inflammation, a defensive mechanism of the body's immune system. Other stimuli include environmental stimuli, oxidative stress, aging and the physiological process. A long-lasting, persistent and excessive inflammatory response is a significant risk factor for developing various chronic inflammatory and infectious diseases. Different nutritional and dietary life styles, whether poor or lacking essential nutritional elements, as well as excess intake, can result in inflammatory complications and loss of function. Nutritional deficiency is linked with several infectious and inflammatory diseases as a cause or consequence. For instance, protein deficiency was reported in orphanages to provoke microbial and fungal complications including Pneumocystis pneumonia. Similarly, protein deficiency is a tell-tale sign of several parasitic diseases. Studies indicate that nutrients, such as amino acids, oligosaccharides, and short-chain fatty acids exert inhibitory and anti-inflammatory functions. These investigations help to understand nutritional contributions to the prevention, treatment and taming of certain inflammatory and infectious diseases. Infectious and inflammatory complications go hand-in-hand with malnutrition. The purpose of this Special Issue is to publish related new, basic and translational findings and clinical trials in this area. Other investigations or review articles were sought to link infectious and inflammatory diseases with nutrients. In addition, novel diagnostic, preventive and therapeutic modalities were invited to aid the development of nutritional strategies for the treatment and/or prevention of inflammation and infection. Original reviews were of particular interest to advance our understanding of signaling pathways, and the molecular and biochemical mechanisms behind the effects of nutrients on inflammatory and infectious diseases.